The individual nutrition education needs among patients with type 2 diabetes at the public health centers in Padang, Indonesia: a cross-sectional study - Puri, Ice Yolanda; Mohd Yusof, Barakatun Nisak; Abu Zaid, Zalina; Ismail, Amin; Haron, Hasnah; Lipoeto, Nur Indrawaty (Multidisciplinary Digital Publishing Institute, 2022)
Background: The Indonesian Public Health Care (PHC) of Management Nutrition Therapy (MNT) guidelines describe that individual nutrition education is aimed to improve quality of MNT services. The guidelines were originally developed for non-communicable diseases (NCDs), not specially for type 2 diabetes mellitus (T2DM) purposes. The reluctance of patients with T2DM to attend individual nutrition education is a common public health care issue in Padang (Indonesia). Methods: The presented cross-sectional study aimed to determine the individual nutrition education needs among people with T2DM. A set questionnaire was distributed to 11 PHC selected from 11 districts in Padang and 179 patients with T2DM were recruited and interviewed. Results: Among the 179 patients with T2DM, 76.5% were females and housewives (49.2%), a slight majority (57.8%) were ≤58 years old and 45.9% had graduated from primary school. The highest numbers of patients with T2DM were in PHC Andalas (20.7%). Some 74.9% (134) of the people with T2DM routinely attended individual nutrition education classes for less than 30 min (60.3%). Patients with T2DM followed individual nutrition education at a PHC every 1–2 months (59.8%), and a majority of the individual nutrition education was given by a medical doctor (57.5%). In contrast, 42.3% of patients with T2DM did not attend individual nutrition education due to a lack of recommendation from a medical doctor and their reluctance (33.3%). Although a majority of patients with T2DM (62.6%) were satisfied with their individual nutrition education, (20.4% of patients with T2DM recommended the availability of booklets during individual nutrition education that can be read at home. Patients with T2DM needed individual nutrition education (88.8%) and the majority (25.1%) requested individual nutrition education topics about diabetes food recommendation. Even though patients with T2DM followed health professionals’ advice (78.2%), however, their HbA1c (76.5%) wasnot reduced. Patients with T2DM agreed that individual nutrition education can increase their knowledge (51.9%), unfortunately, they still have difficulty to control their blood glucose (5.6%). Conclusions: According to the patients with the T2DM perspective stated above, it is crucial to develop the tool kits and educate patients with T2DM following the Diabetes Nutrition Education (DNE) curriculum to improve glycemic control.